Implementasi Integrasi Gaya Kepemimpinan Servant Leadership, Demokratis, dan Otokratis Terhadap Pertumbuhan Gereja - Dandel, Fredrik; Widiada, Gede; Hadi, Nathanael Yitshak (IAKN TORAJA, 2025)
This study aims to analyze the implementation and integration of servant leadership, democratic, and autocratic leadership styles in relation to church growth. The growing phenomenon of newly established local churches presents challenges for pre-existing churches, including congregation shifts. Therefore, church leaders must adopt appropriate leadership styles to guide their congregations both socially and spiritually. This research employs a descriptive qualitative approach using literature review, limited interviews, and selective observation techniques. The findings indicate that autocratic leadership is effective during crises but may restrict congregational participation if applied excessively. Democratic leadership fosters congregational involvement but may slow down decision-making processes. Meanwhile, servant leadership is considered the most ideal, as it builds strong relationships and promotes sustainable spiritual growth and fellowship. In conclusion, churches need to adopt adaptive and contextual leadership styles rooted in Christian values in order to grow in a healthy and sustainable manner.